Examination of the Right of a Female Child to Inheritance: Eastern Nigeria Context - Kehinde, Adeola Olufunke; IYANIWURA , SUNDAY KOLAWOLE; ADIMOHA , CHIKAODILI (PRAWO i WIĘŹ, 2022)
Currently, the nation (Nigeria) is no doubt, in its worst economic periods because of the global economic downturn which brought about the economic recession (slacking of business and industrial activity). Those at the helm of affairs grapple daily with the numerous problems that are attendant on economic depression to save the country from total collapse. In addition to the economic depression is the growing cases of disputes emanating from the female child inheritance in Eastern Nigeria which covers Anambra, Abia, Enugu, Imo, and Ebonyi States. The status of women has, through the ages, been a cause for grave concern in every culture and every clime. In some areas of the globe, it has passed the stage of sympathetic concern and has entered an era of aggressive feminism.In Eastern Nigeria, the right to inherit property is determined by the customary law which did not accord any recognition on a woman except as property of her husband or parents (chattel). This paper examines the right of a female child to inherit property in Eastern Nigeria, states categorically the weaknesses of customary laws in protecting the interest of a female child, the current position of Superior Courts of record in Nigeria examines both local and international instruments put together for the protection of women and makes recommendations.